1983
DOI: 10.1161/01.cir.67.2.276
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous nitroglycerin in the treatment of spontaneous angina pectoris: a prospective, randomized trial.

Abstract: SUMMARY A prospective, randomized study of i.v. nitroglycerin (TNG) 276 included a randomized control, which is especially important in assessing the therapeutic efficacy of antianginal agents because of the spontaneous variability in the occurrence of ischemic episodes.'6We therefore performed a prospective, randomized trial comparing the therapeutic effect of i.v. TNG with that of oral isosorbide dinitrate (ISDN) in combination with 2% nitroglycerin ointment (NO) in patients with repetitive episodes of spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1984
1984
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…First, the blood concentration of NTG achieved in the ischemic territory, equal to Ϸ1 g͞ml, was higher than that found in patients treated with sublingual, transdermal, and i.v. NTG administration (33,34). It remains to be determined whether similar effects occur at lower doses.…”
Section: Discussionmentioning
confidence: 99%
“…First, the blood concentration of NTG achieved in the ischemic territory, equal to Ϸ1 g͞ml, was higher than that found in patients treated with sublingual, transdermal, and i.v. NTG administration (33,34). It remains to be determined whether similar effects occur at lower doses.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent advances in medical management (aggressive use of f-blockers, calcium entryblocking agents, and intravenous nitroglycerin) have had a beneficial effect on symptoms during the acute phase. [15][16][17] However, the recent randomized study from Johns Hopkins'5 demonstrated a very high rate of "failure of medical therapy"; at 4 months in the nifedipine-treated group the failure rate was 44% and in those not treated with nifedipine it was 62%.…”
Section: Treatmentmentioning
confidence: 99%
“…These therapies control pain but not all episodes of myocardial ischemia. 17 Moreover, many episodes of myocardial ischemia are painless, and it seems reasonable that ischemia with or without pain is the precursor of myocardial infarction and death; thus, it is easy to understand why modern pharmacologic therapy has not had a great impact in this disorder. '5-17 However, aspirin administered for 4 months had a beneficial effect on the incidence of myocardial infarction at 4 months and 1 year and the incidence of cardiac death at 1 year but not at 4 Coronary bypass surgery.…”
Section: Survivalmentioning
confidence: 99%
“…Thus, more than three fourths of the patients failing medical treatment occurred within 18 months of randomization. In the first 30 days, the crossover rate was higher among patients with type 2 than among those with type 1 (19 Figure 2). When mortality was analyzed according to prerandomization stratification by clinical presentation, there were also no significant differences shown in survival ( Figures 3A, 3B).…”
Section: Outcomes Of Initial Hospitalization and Graft Patencymentioning
confidence: 98%